Meningkatkan Hasil Belajar Siswa pada Pembelajaran IPS dengan Metode Problem Solving - Emilia Fernanda (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2017)
Students of grade 4 SDN 21 Batang Anai Kabupaten Padang Pariaman in learning process used to be passive. Teacher also often used the expository method. This is a classroom action research with two cycles that aimed to improve students’ learning achievement (cognitive, affective, and psychomotor domains) through implementation of problem solving method in social subject learning. In cycle I, students’ score of cognitive domains is 6.46, students’ score of affective domain is 6.49, and students’ score of psychomotor domain is  6.49. In cycle II, students’ score of cognitive domains is 8.23, students’ score of affective domain is 8.24, and students’ score of psychomotor domain is 8.03.